GIWAXS‐SIIRkit: scattering intensity, indexing and refraction calculation toolkit for grazing‐incidence wide‐angle X‐ray scattering of organic materials. Issue 4 (12th June 2020) - Savikhin, Victoria; Steinrück, Hans-Georg; Liang, Ru-Ze; Collins, Brian A.; Oosterhout, Stefan D.; Beaujuge, Pierre M.; Toney, Michael F.
Abstract : A software package is described for grazing‐incidence wide‐angle X‐ray scattering geared towards weakly ordered materials, with functionality including scattering intensity normalization/uncertainty estimation, scattering pattern indexing and refractive shift correction. Abstract : Grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) has become an increasingly popular technique for quantitative structural characterization and comparison of thin films. For this purpose, accurate intensity normalization and peak position determination are crucial. At present, few tools exist to estimate the uncertainties of these measurements. Here, a simulation package is introduced called GIWAXS‐SIIRkit, where SIIR stands for scattering intensity, indexing and refraction. The package contains several tools that are freely available for download and can be executed in MATLAB. The package includes three functionalities: estimation of the relative scattering intensity and the corresponding uncertainty based on experimental setup and sample dimensions; extraction and indexing of peak positions to approximate the crystal structure of organic materials starting from calibrated GIWAXS patterns; and analysis of the effects of refraction on peak positions. Each tool is based on a graphical user interface and designed to have a short learning curve. A user guide is provided with detailed usage instruction, tips for adding functionality and customization, and exemplary files.